EMPOWERING THE YOUTH: THE ROLE OF PRINT MEDIA IN PROMOTING CHILD RIGHTS - Mishra, Kalpit; Singh, Shailendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Print media in Bhopal is essential to public education and child rights advocacy. Child rights concerns such as child maltreatment, marriage, work and education are covered by the media through surveys, interviews and content analysis. Print media effectively promotes awareness and initiates policy discussions, empowering youth and fostering informed and involved communities despite limited resources and low public engagement. This demonstrates how crucial NGOs and print media resources are to Bhopal’s awareness and development.